VACCINATION OF PREMATURE INFANTS AND CHILDREN WITH CONGENITAL HEART DISEASE IN IRKUTSK USING CONJUGATED PNEUMOCOCCAL VACCINES - S. V. Il'ina; Y. I. Lyisanov (Union of pediatricians of Russia, 2013)
Study aim: analyzing the results of pneumococcal infection vaccination conducted to reduce infantile morbidity and mortality in 2011-2012 at the expenses of the Irkutsk municipal budget. Patients and methods. Vaccination using the 7- and 13-valent pneumococcal conjugated vaccine was conducted for more than 700 risk group children: premature infants, children with congenital heart diseases or bronchopulmonary dysplasia from 2 months to 2 years of age. 193 vaccinated children had been observed for 1.5 years. 30% of premature infants and 46% of children with congenital heart diseases were vaccinated using the PCV7/PCV13 vaccine at the age of 2-6 months, 52 and 40% - at the age of 7-11 months, accordingly. The PCV7/PCV13 vaccine was administered together with other vaccines of the national preventive vaccination calendar in 65% of cases. Results. Rate of general post-vaccinal reactions (body temperature increase from 37.6 to 38.0oC) - 4%; no local reactions were registered. No other unfavorable phenomena were noted in the post-vaccinal period. No cases of pneumonia, meningitis, acute otitis media and bronchoobstructive syndrome were registered within the observation period. Conclusions: pneumococcal infection vaccination of premature infants with congenital heart diseases and bronchopulmonary dysplasia conducted in Irkutsk proved high efficacy and safety of the used vaccine - PCV7/PCV13.